1983
DOI: 10.1084/jem.157.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Tthy alloantigen expression in the neonatal mouse. The Tthy-bearing thymocyte is a precursor for the peripheral cells expressing Tind and Tsu.

Abstract: The T cell alloantigen Tthyd appears on a subpopulation of thymocytes in mice bearing the Igh-1d or e heavy chain haplotype. Ontogenetic studies have suggested that this antigen precedes the appearance of two other T cell alloantigens in the same linkage group, Tindd and Tsud. The purpose of this study was to determine if the Tthy-bearing cell is a precursor for cells in the periphery expressing Tind and Tsu. CAL-20 mice were treated at 48-h intervals beginning on the day of birth with a monoclonal antibody re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Tests of a panel of monoclonal antibodies specific for Tthy d, Tind d, and Tsu d found that none reacted with cytotoxic effector or MLR-reactive T ceils (G. M. Spurll, M. Frye, L. Riendeau, A. Finnegan and F. L. Owen, manuscript in preparation). Furthermore, Tinda-positive and Tsua-positive cells are ontogenetically related in that Tthyd-positive thymocytes are precursors of both of these mature T cell subsets (30). The antigen receptors used by this family of regulatory T cells may be distinct from those used by the majority of T cells, which see antigen in the context of H-2 molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Tests of a panel of monoclonal antibodies specific for Tthy d, Tind d, and Tsu d found that none reacted with cytotoxic effector or MLR-reactive T ceils (G. M. Spurll, M. Frye, L. Riendeau, A. Finnegan and F. L. Owen, manuscript in preparation). Furthermore, Tinda-positive and Tsua-positive cells are ontogenetically related in that Tthyd-positive thymocytes are precursors of both of these mature T cell subsets (30). The antigen receptors used by this family of regulatory T cells may be distinct from those used by the majority of T cells, which see antigen in the context of H-2 molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal Antibodies. Monoclonal anti-Tpre d (F.6.9.1), Tthy d (17IIC6), Tind d (9IIIA2), and Tsu d (13IIIB4)antibodies have been described (1)(2)(3)(4)(5)(6)(7)(8). These antibodies were conjugated with fluorescein isothiocyanate (FITC) and used with mouse anti-FITC, affinity-purified polyclonal antibody, and complement to iyse cells.…”
mentioning
confidence: 99%
“…Cells bearing CT determinants are a subpopulation of cells. An in vivo model for depletion of cells expressing the antigenic determinants Tthy, Tind and Tsu was developed by injecting neonatal mice with monoclonal anti-Tthy antibody and maintaining mice on this regime until 6-8 weeks of age (Keesee & Owen 1983). This protocol resulted in the apparent depletion of cells in the animal which expressed Tthy, Tind, and Tsu but did not alter the percentage or frequency of cells expressing Thy 1.2, Lyt 1.2 or Lyt 2.2.…”
mentioning
confidence: 99%